Disorder mediated biexcitonic beats in semiconductor quantum wells - Meier, Torsten; Albrecht, T.F.; Bott, K.; Schulze, A.; Koch, M.; Cundiff, S.T.; Feldmann, J.; Stolz, W.; Thomas, P.; Koch, S.W.; Göbel, E.O. (Physical Review B)
Beats in the transient four-wave-mixing signal from strongly inhomogeneously broadened semiconductor quantum wells are observed. Based on their phase and polarization properties, the beats are assigned to biexcitons in the mesoscopically disordered material. With increasing excitation intensity a halving of the beat period is observed and is accurately reproduced by calculations including fifth-order contributions.

Femtosecond Spectroscopic Signatures of Electronic Correlations in Conjugated Polyenes and Semiconductor Nanostructures - Meier, Torsten; Mukamel, S. (Physical review letters)
Electronic correlation effects which can be directly probed by ultrafast four-wave mixing are predicted using the electronic-oscillator representation of conjugated polyenes. Comparison with inorganic semiconductors is made possible since the semiconductor Bloch equations projected onto the lowest exciton are obtained as a limiting case. A sign difference in a nonlinear scattering potential clearly shows up in the Wigner spectrogram representing the time and frequency resolved signal.

Field-induced exciton ionization studied by four-wave mixing - Meier, Torsten; Koch, M.; von Plessen, G.; Feldmann, J.; Koch, S.W.; Thomas, P.; Göbel, E.O.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Hot Carriers in Semiconductors)
The dynamics of carriers induced by electric fields in semiconductor superlattices has received much interest in recent years. Phenomena like Bloch oscillations and negative differential velocity in these structures have been studied using a variety of experimental techniques [1–5]. One particular point of interest has been the transition of the miniband regime to the Bloch oscillation regime with increasing electric field [6,7]. Cw spectra of strongly-coupled superlattices have evidenced that this transition is concomitant with a rapid field-induced ionization of the zero-field miniband exciton [5,8]. While it has been pointed out from the theoretical side that the field-induced ionization process strongly influences the coherent dynamics in the transition region [9], no systematic experimental investigation of the ionization process has been carried out so far. One interesting question that such an investigation could help to answer is to what extent this ionization process differs from the well-documented case of field-induced exciton ionization in bulk semiconductors.

Equilibrium and nonequilibrium optical effetcs in semiconductor heterostructures - Meier, Torsten; Koch, S.W.; Hader, J.; Je, K.-C; Rossi, F.; Thomas, P. (Frontiers in Nanoscale Science of Micro/Submicro Devices)

Phonon-Induced Suppression of Bloch Oscillations in Semiconductor Superlattices: a Monte Carlo Investigation - Meier, Torsten; Rossi, F.; Thomas, P.; Koch, S.W.; Selbmann , P.E.; Molinari, E. (Hot Carriers in Semiconductors)
The progress in the generation of ultrashort laser pulses, together with the development of spectroscopies on this time-scale, has led to a series of experiments which give new insight into the microscopic carrier dynamics in semiconductors. In particular, the energy relaxation of photoexcited carriers has been widely investigated. At the same time, recent progress in the fabrication and characterization of semiconductor heterostructures and superlattices allows a detailed study of a new class of phenomena induced by an applied electric field, such as Bloch oscillations1,2. Both classes of phenomena typically occur on a pico- or femtosecond time-scale, where the coupling between coherent and incoherent phenomena is known to play a dominant role3. Therefore, an adequate theoretical model of the ultrafast dynamics on this time-scale must account for both coherent and incoherent effects on the same kinetic level.

Diamond (111) and (100) surface: ab initio study of the atomic and electronic structure - Scholze, A.; Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Materials Science and Engineering: B)

Structure of the diamond (111) surface: Single-dangling-bond versus triple-dangling-bond face - Scholze, A.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Dimerized, buckled, or ideal chains on the diamond (111)2 × 1 surface? - Schmidt, Wolf Gero; Scholze, A.; Bechstedt, F. (Surface Science)

Annihilation of delocalized positrons: a comparison of diamond and silicon - Schmidt, Wolf Gero; Verwoerd, W.S (Physics Letters A)

Se-induced 3d core-level shifts of GaAs(110) - Käckell, Peter; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Applied Surface Science)

Adsorption of group-V elements on III–V (1 1 0) surfaces - Schmidt, Wolf Gero (Surface Science Reports)

Diamond (111) and (100) surface reconstructions - Scholze, A.; Schmidt, Wolf Gero; Bechstedt, F. (Thin Solid Films)

Phonons at III–V (110) surfaces - Schmidt, Wolf Gero; Bechstedt, F.; Srivastava, G.P. (Surface Science)

3d core-level shifts at - Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Surface Science)

Atomic Structure of the Sb-Stabilized GaAs(100)-(2×4) Surface - Esser, N.; Shkrebtii, A. I.; Resch-Esser, U.; Springer, C.; Richter, W.; Schmidt, Wolf Gero; Bechstedt, F.; Del Sole, R. (Physical Review Letters)

Optical Properties of Ordered As Layers on InP(110) Surfaces - Santos, Paulo V.; Koopmans, B.; Esser, N.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

Geometry and electronic structure of GaAs(001)(2×4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Adatoms and vacancies on the diamond(111) surface - Bechstedt, F; Schmidt, Wolf Gero; Scholze, A (Europhysics Letters (EPL))

Atomic structures of GaAs(100)-(2 × 4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Surface Science)

Coherent effects induced by static and time-dependent electric fields in semiconductors - Meier, Torsten; von Plessen, G.; Thomas, P.; Koch, S.W. (Physical Review B)
Coherent effects are analyzed that are induced by homogeneous electric fields in photoexcited semiconductors. Extended semiconductor Bloch equations are presented, which include the applied electric field, in addition to the many-body Coulomb contributions in the time-dependent Hartree-Fock approximation. These equations are solved for a one-dimensional tight-binding model of a semiconductor superlattice. Linear and nonlinear optical signals associated with the coherent field-induced effects are calculated. For the case of a static electric field, the influence of the Coulomb interaction, which is treated on the Hartree-Fock level for a contact potential approximation, on the Bloch oscillations, and on their counterpart in the frequency domain, the Wannier-Stark-ladder, is analyzed. For a time-dependent electric field, dynamic localization, i.e., the localization of electrons due to an oscillating electric field, is analyzed. It is predicted that the dynamic localization should be observable in semiconductor superlattices even in the presence of Coulomb interaction.